Nonlinear Dynamics of Semiconductor Lasers Under Repetitive Optical Pulse Injection - Lin, Fan-Yi; Tu, Shiou-Yuan; Huang, Chien-Chih; Chang, Shu-Ming (IEEE journal of selected topics in quantum electronics, 2009)
In this paper, nonlinear dynamics of semiconductor lasers under repetitive optical pulse injection are studied numerically. Different dynamical states, including pulsation and oscillation states, are found by varying the intensity and the repetition rate of the injection pulses. The laser is found to enter the chaotic pulsation (CP) states and chaotic oscillation (CO) states through individual period-doubling routes. Mapping and corresponding Lyapunov exponents of these dynamical states are plotted and examined in the parameter space. Moreover, the bandwidths of the chaos states found are investigated, where the bandwidths of the CP states observed at the strong injection regime are two to four times broader than the bandwidths of the CO states found at the weak injection regime. In this paper, frequency-locked states with different winding numbers, the ratio of the oscillation frequency, and the repetition frequency of the injection pulses are also studied. Both the cases for repetition frequency above and below the relaxation oscillation frequency are examined. The winding numbers of the frequency-locked states reveal a Devil's staircase structure, where a Farey tree showing the relations between the neighboring states is constructed.